2013
DOI: 10.1371/journal.pone.0073896
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Network Analysis of ETV1 Reveals KCTD10 as a Novel Prognostic Biomarker in Gastrointestinal Stromal Tumor

Abstract: BackgroundPrognostic biomarkers are required for risk stratification therapy in the patients with gastrointestinal stromal tumor (GIST). In this study, we aimed to identify prognostic biomarkers in GIST. We assessed the prognostic value of E twenty-six variant 1 (ETV1), a recently identified transcription factor unique to GIST. We also examined the clinical utility and functions of its downstream gene, potassium channel tetramerization domain containing protein 10 (KCTD10).MethodsThe levels of ETV1 and KCTD10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Promoter analysis showed that KCTD10 can be regulated positively by SP1 and negatively by AP-2 transcription factors [5] . In a recent study, KCTD10 was reported to be regulated by a novel transcription factor ETV1 which is unique to gastrointestinal stromal tumors (GISTs), and RNAi-mediated silencing of KCTD10 increased cell invasion, suggesting that KCTD10 function as a tumor suppressor protein [7] . However, the exact functions of KCTD10 in mammalian development remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Promoter analysis showed that KCTD10 can be regulated positively by SP1 and negatively by AP-2 transcription factors [5] . In a recent study, KCTD10 was reported to be regulated by a novel transcription factor ETV1 which is unique to gastrointestinal stromal tumors (GISTs), and RNAi-mediated silencing of KCTD10 increased cell invasion, suggesting that KCTD10 function as a tumor suppressor protein [7] . However, the exact functions of KCTD10 in mammalian development remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very likely that there are other potential GIST risk-related genes, as suggested by our previous gene microarray (unpublished data). In agreement with this, the potassium channel tetramerization domain containing protein 10 (KCTD10) has been shown to correlate with GIST prognosis [31] . Future studies and identification of novel prognostic biomarkers will help further stratify risk groups and direct treatment strategies for GIST.…”
Section: Discussionmentioning
confidence: 71%
“…35 Kubota et al reported that ETV1 expression in GIST had no prognostic significance, but its downstream gene, KCTD10, was associated with a favorable prognosis in patients with GIST. 36 We also reported that GIST cases with DNA methylation, such as REC8, PAX3 and p16, had a poor prognosis. 37 The preoperative assessment of these biological markers may enable follow-up strategies for potentially lowmalignant GIST.…”
Section: Discussionmentioning
confidence: 86%